Intonational phonology and prosodic hierarchy in Malay - Hamzah, Diyana (2014)
This paper presents original data in support of a new model of intonational phonology for Malay as spoken in Singapore. Building on the Autosegmental-Metrical approach (Beckman & Pierrehumbert, 1986), we propose that intonational variation in Malay can be explained in terms of underlying sequences of abstract tonal units (H and L), which are aligned to the edges and internal syllables of prosodic phrases organized in a hierarchy. Data was drawn from a production experiment (Hamzah, 2012) involving declarative utterances under different focus patterns in a question-answer context, as well as from story-telling interviews and TV interviews. We find evidence for at least three levels of prosodic organization: (i) an accentual phrase which comprises one or more words and bears an L and H tone at its left and right edges, respectively, (ii) an intermediate phrase, which serves as the domain of catathesis, and (iii) an intonational phrase, which may span the entire utterance and bears an additional H or L tone at its right edge. Differences in F0 peak alignment for focused words support the presence of a focus pitch accent. We outline a series of follow-up studies for extending the model further.